P126 MULTIPLE SIGNALING PATHWAY DEFECTS IN THE INTESTINAL STEM CELL NICHE LIKELY TRIGGER CD-LIKE ILEITIS IN SAMP1/YITFC MICE. (7th February 2019) - Buttò, Ludovica F; Pelletier, Adam; Zhao, Nan; Osme, Abdullah; Hager, Christopher; Ghannoum, Mahmoud; Sekaly, Rafick-Pierre; Cominelli, Fabio; Dave, Maneesh
Abstract: Intestinal epithelial barrier dysfunction is considered as a risk factor in the pathogenesis of Crohn's disease (CD), and since there is no FDA approved therapy available, there is a need for identifying a relevant model to study and test therapies to correct this defect. Previously, we demonstrated that inflammatory environment of CD affects properties of intestinal stem cell (ISC) niche, ablating its ability to form enteroids (EnOs) in our mouse model for CD-like ileitis (SAMP/YitFc, SAMP) (doi.org/10.1016/S0016-5085(17)32213-8). However, EnOs from SAMP mice even prior to disease onset (5-wks, SAMP-5) harbor impaired features, such as smaller size (2.6 ± 0.4 vs 3.9 ± 0.2 fold to ctrl at day 1, P =0.003), number (0.6 ± 0.1 fold to ctrl, P =0.000), reduced viability (63.7%±7.5 vs ctrl P =0.003) and rudimental branching complexity [cyst-like structures (42.7%±2.3 vs 11%±1.2)], compared to controls (ctrls). These EnOs produce exacerbated expression of genes involved in epithelial secretory cell functions when challenged with purified bacterial ligands, such as LPS [higher Muc2 (10.8 ± 3.2 vs 2.5 ± 1.8 P =0.00), Lyz (11.0 ± 5.2 vs 1.1 ± 0.4 P =0.00), Reg3γ (6.7 ± 9.9 vs 1.1 ± 0.5 P =0.04), Crp (7.4 ± 5.4 vs 1.3 ± 0.6 P =0.05), and Defa1 (4006.0 ± 1472.5 vs 2.1 ± 0.7 P =0.00) mRNA vs AKR EnOs]. To further investigate this phenotype, we generated the first high-resolution transcriptional profile of SAMP ISC niche by laser capture microdissection and RNA sequencing. We found that signaling pathways involved in the cellular energy machinery were dramatically reduced in inflamed SAMP (25-wks, SAMP-25) ISC niche compared to that of inflammation-free mice [mitochondrial energy metabolism (P ≤ 0.00, Padj ≤ 0.002, normalized enrichment score NES ≤ -2.4); oxidative phosphorylation (P ≤ 0.00 Padj ≤ 0.001 NES ≤ -2.5)]. Fibrosis (P ≤ 0.04 Padj ≤ 0.09 NES ≤ 1.3) and UPR (P ≤ 0.01 Padj ≤ 0.03 NES ≤ 1.5) pathways were enriched in SAMP-25 ISC niche compared to ctrls, but not to that of SAMP-5 mice. Bile acid metabolism (P ≤ 0.00, Padj ≤ 0.002 NES ≤ -1.8), ROS (P ≤ 0.001 Padj ≤ 0.003 NES ≤ -1.8), Wnt3a (P ≤ 0.001 Padj ≤ 0.01 NES ≤ -1.8), and Notch1 (P ≤ 0.001 Padj ≤ 0.02 NES ≤ -1.8) pathways were decrease in SAMP-25 ISC niche compared to ctrls, but not to that of SAMP-5 mice. Collectively, these data suggest that multiple signaling pathways contribute to ISC niche defect in SAMP mice, and that many key biological functions are already altered prior to ileitis onset and may be responsible for disease initiation. Finally, the evidence that altered gene expression is maintained in ex vivo expanded EnOs indicates that these cultures recapitulate reactive epithelial changes specific of experimental CD. This aspect is of paramount importance since it emphasizes the physiologically relevant value of EnOs generated from SAMP mice, rather than those originated from healthy individuals, to mimic CD-like ileitis.